Green tide to green fuels: TG–FTIR analysis and kinetic study of Ulva prolifera pyrolysis. (1st September 2015) - Ceylan, Selim; Goldfarb, Jillian L.
Highlights: Distributed Activation Energy Model applied to Ulva prolifera pyrolysis. Model and experimental data in good agreement to predict activation energy. Ulva prolifera shows relatively low activation energy compared to other macroalgae. Evolved gas analysis shows CO2 emission decreasing with temperature. Methane evolution increases with temperature, peaks at 800 °C. Abstract: The world grapples with identifying renewable replacements for fossil fuels. Ulva prolifera, a macroalgae species that has caused green tides in China and Europe, represents a possible source of renewable energy. Given its low lipid content, thermochemical conversion techniques such as pyrolysis may be more suitable than biochemical techniques. We apply the Distributed Activation Energy Model to determine the activation energy of pyrolysis of U. prolifera from thermogravimetric data with combined evolved gas analysis via FTIR. Correlation coefficients for the DAEM were greater than 0.98 at each conversion; the apparent activation energy ranged from 130 to 152 kJ/mol, in good accord with the literature. Three stages of decomposition were noted over the entire temperature range; below 110 °C mass loss due to moisture removal. The largest stage of pyrolysis occurred between 190 and 400 °C with peak mass loss conversion rates up to 8.1 wt% per minute at 20 °C/min. The concentration of CO2 in the evolved gas peaked along with mass loss rate at 242.7 °C. Stage III of pyrolysis saw a slow mass loss rate and a significant amount of methane from the macroalgae. Given its low energy, nutrient, land and maintenance requirements to grow, tolerance to a variety of environmental conditions, and low pyrolysis activation energies (as compared to other macroalgae), thermochemical conversion via pyrolysis is a viable way to extract energy from this seaweed species.